The disappearance of the perfect 10: Evaluating rule changes in women's artistic gymnastics - Kerr, R.; Obel, C. (The International Journal of the History of Sport, 2015)
The 2004 Olympic Games saw a range of judging scandals in the sport of artistic gymnastics that prompted the International Gymnastics Federation to make changes to the sport's judging system. Therefore, following these games, the International Gymnastics Federation reworked the gymnastics scoring system, where the most prominent change was the removal of the `perfect 10` as the highest score possible, to be replaced by an open-ended scoring system. The goal of this paper is to examine the effectiveness of the open-ended system that was introduced in 2006 through examining some of the sport's key values - an approach loosely aligned with broad internalism. It is suggested that the dual purposes of analysing what is achieved and the manner of achieving it are key values of the sport and are differentiated through the way judging utilises two categories known, in gymnastics, as `difficulty` and `artistry`. This paper argues that the method of judging `difficulty` is an improvement on previous judging methods. Our analysis of the definition and judging of `artistry` in artistic gymnastics, however, reveals a less certain result.